Bengkulu Brovape Promotion Strategy in Attracting Consumer Buying Interest (Study of Marketing Communication Strategy at Brovape Stores in Bengkulu) - Ivan Satria Negara; Dedi Supriyadi; Yudisani Yudisani (Penerbit Jurnal Indonesia, 2022)
The title of this research is